Cutting Parameters and the Machinability Performance - Mohamed, Prof. Ts. Dr. Saiful Bahri; Ab Rashid, Prof. Madya Dr. Radzuwan; Muhamad @ Mohd Saufi, Ts. Dr. Martini (Springer Verlag, 2019)
Optimizing cutting parameters is very significant to obtain good machined surface and meet engineering specifications. It is also can save energy, reduce waste, save processing time, and increase tool life.